Cleaning up our acts: Psychological interventions to reduce engine idling and improve air quality. (April 2021) - Abrams, Dominic; Lalot, Fanny; Hopthrow, Tim; Templeton, Anne; Steeden, Ben; Özkeçeci, Hilal; Imada, Hirotaka; Warbis, Sarah; Sandiford, Dominic; Meleady, Rose; Fell, Emily; Abrams, Zoe; et al.
Abstract: A large-scale field experiment tested psychological interventions to reduce engine idling at long-wait stops. Messages based on theories of normative influence, outcome efficacy, and self-regulation were displayed approaching railway crossing on street poles. Observers coded whether drivers ( N = 6049) turned off their engine while waiting at the railway crossings (only 27.2% did so at baseline). Automatic air quality monitors recorded levels of pollutants during barrier down times. To different degrees, the social norm and outcome efficacy messages successfully increased the proportion of drivers who turned off their engines (by 42% and 25%, respectively) and significantly reduced concentrations of atmospheric particulate matter (PM2.5 ) 2 m above ground level. Thus, the environment was improved through behavior change. Moreover, of both practical and theoretical significance, there was an 'accelerator effect', in line with theories of normative influence whereby the social norm message was increasingly effective as the volume of traffic increased. Highlights: Observed 6, 049 drivers' engine idling whilst waiting at railway level crossings. Baseline showed only 27.2% switched off their engines. Tested persuasive messages using social norm, outcome efficacy, private self-focus. Improved air quality, and increased compliance by 42% (norms) and 13% (efficacy). Effect of social norms effect on idling and PM2.5 accelerated as queues lengthened.